Low-grade glioma surgery in intraoperative magnetic resonance imaging: results of a multicenter retrospective assessment of the German Study Group for Intraoperative Magnetic Resonance Imaging - Coburger, Jan; Merkel, Andreas; Scherer, Moritz; Schwartz, Felix; Gessler, Florian; Roder, Constantin; Pala, Andrej; König, Ralph; Bullinger, Lars; Nagel, Gabriele; Jungk, Christine; Bisdas, Sotirios; et al. (Neurosurgery, 2016)
AbstractBACKGROUND:. The ideal treatment strategy for low-grade gliomas (LGGs) is a controversial topic. Additionally, only smaller single-center series dealin
Published Online: October 28, 2015
Gesehen am 04.05.2020